Investment Perspective According to Behavioral Finance Science - Al-Anizi, Sa’ad (Journal of Economics and Administrative Sciences, 2010)
The first thing that comes to mind is the highly important question of whether there were some effects of human behavior and its fluctuations on the theories of the efficient market and the contemporary investment portfolio. According to what has been said by the proponents of these two theories; when the optimal return is realized, the efficiency of the market is achieved in terms of perfect information on prices and risk that supposed to be predetermined in a rational way. he other question that imposed here is “at what time people should be rational in their investments in the security markets ?”. This means that investors are rational for their efforts devoted to utility maximization, which are perceived as a result of investing their wealth in the best possible manner. Then, can those two questions be achieved in practice? Many ontological aspects are influenced in their relations by emotions and feelings more than by money as a financial resource . Investors may take irrational financial decisions because of the dominance of those emotions and feelings compared with what investors do toward other actions in their public and special daily life. Understanding investors financial awareness without taking into account the human action is considered as an outstanding problem which can be assimilated as an attempt to sail with compass, but without guided maps. The importance and necessity of human psychological factor are arise when we are talking about investing common stocks in the security market. Then, this means that issues directing investment decisions of individuals in financial assets whether they were stocks or bonds, can be only interpreted with referring to principles of human behavior. Absolutely there is no exaggeration if we said that the market in general be advanced, lagged behind , prospected , and crept when making collective decisions in buying securities through viewing psychological factors which capture individuals behaviors after information being collected and analyzed. The validity of an efficient market theory has been widely accepted by its proponents for a long time lasting almost a century so that any research on the psychological aspects of a security market encountered by objection till a close time of ten years .